Elucidating the Inhibitory Mechanisms of Magnolol on Rat Smooth Muscle Cell Proliferation - Chieh-Hsi Wu; Chih-Wen Chen; Ho-Chih Chen; Weng-Cheng Chang; Min-Ji Shu; Jui-Sung Hung (Elsevier, 2005)
The pathological mechanism of percutaneous transluminal coronary angioplasty-induced restenosis has been attributed to outgrowth of vascular smooth muscle cells. Pretreatment with antioxidants has been shown to reduce restenosis. Magnolol, an active compound of Magnolia officinalis, has exhibited approximately 1,000 times more potent antioxidant effects than alpha-tocopherol. In this study, we demonstrate, using cytometric analysis, an approximate 61% reduction of smooth muscle cells progressing to the S-phase by 0.05 mg/ml of magnolol. A BrdU incorporation assay also showed a significant reduction (73%) of DNA synthesis using 0.05 mg/ml of magnolol. The protein level of the proliferating cell nuclear antigen was suppressed by approximately 48% using 0.05 mg/ml of magnolol. This was in agreement with the promoter activity of nuclear factor-kappa B, which was also attenuated by 0.05 mg/ml of magnolol. Since receptor interacting protein and caspase-3 protein expression levels were both increased by magnolol in a dose-dependent manner, the apoptotic pathway may mediate the inhibition of cell growth. Our finding that malondialdehyde formation was significantly inhibited by 0.05 mg/ml of magnolol further supported the antioxidant effect of magnolol. These studies suggest that magnolol might be a potential pharmacological reagent in preventing balloon injury-induced restenosis. Keywords:: percutaneous transluminal coronary angioplasty, restenosis, magnolol, neointima formation